Method for manufacturing polarizing plate protective film
Patent Information
- Application Number
- CN202280026459.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-06
- Filing Date
- 2022-03-07
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-03-07
AI Technical Summary
In the existing technology, the adhesion between the polarizer protective film of cyclic olefin polymers and the polyvinyl alcohol film is insufficient, making it difficult to meet the requirements of high performance.
By controlling the relationship between membrane conveying speed and residual solvent amount in the raw material membrane manufacturing process and processing process, especially the residual solvent amount of 1 to 15% by mass before the first stage stretching and the stretching ratio of 1.1 to 2.0 times, and the residual solvent amount of 0.1 to 0.5% by mass during the second stage stretching, and the conveying speed satisfying V1 < V2, stretching treatment is performed to improve the membrane surface condition.
The adhesion between the cyclic olefin polymer polarizer protective film and the polyvinyl alcohol film was improved, the degradation of film strength was suppressed, and the adhesion strength and planarity of the polarizer protective film were ensured.
Smart Images

Figure CN117157564B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing a polarizing protective film. More specifically, it relates to a method for manufacturing a polarizing protective film containing a cyclic olefin polymer, wherein the adhesion to polyvinyl alcohol-based films is improved. Background Technology
[0002] As a polarizer protective film used in polarizers of liquid crystal displays, cellulose ester polymers such as triacetyl cellulose are suitable and frequently used due to their low birefringence.
[0003] Polarizing films are generally composed of a film (hereinafter also called "polarizing film", "polarizer film" or "polarizer thin film") formed by adsorbing and oriented polyvinyl alcohol film with iodine and dye, and a transparent polymer (resin) film layer stacked on both sides of the film.
[0004] Triacetyl cellulose protective films have been commonly used as transparent polymer film layers in the past, but various improvement methods have been proposed in response to the urgent need for high-level performance from various perspectives in recent years.
[0005] For example, Patent Document 1 discloses a technique for controlling the angular unevenness of the slow axis direction of a cellulose ester-based protective film during the fabrication of a polarizer protective film.
[0006] On the other hand, compared with cellulose ester polymers, cyclic olefin polymers have superior advantages such as transparency, optical properties, and durability. Therefore, the expectation of using polarizing protective films made of cyclic olefin polymers in display devices such as liquid crystal displays is increasing year by year.
[0007] However, the protective films of cyclic olefin polymers, like those of cellulose ester polymers, still fall short of expectations for high performance. A new problem has been discovered: after applying the improved technology described in Patent Document 1 above, there is room for improvement in the adhesion between the polarizing film and the polarizing protective film.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: Japanese Patent Application Publication No. 2002-311240 Summary of the Invention
[0011] The present invention was made in view of the above-mentioned problems and circumstances, and its solution is to provide a method for manufacturing a polarizing protective film containing a cyclic olefin polymer with improved adhesion to polyvinyl alcohol-based polarizing films.
[0012] To solve the above-mentioned problems, the inventors investigated the causes of these problems and found that by controlling the relative relationship between the film conveying speed in the raw material film manufacturing process and the processing process, and the amount of residual solvent in the film during stretching within a certain range, the surface condition of the film can be improved, and the above-mentioned problems can be solved, thus obtaining the present invention.
[0013] That is, the above-mentioned problems of the present invention are solved by the following method.
[0014] 1. A method for manufacturing a polarizing protective film, characterized in that the polarizing protective film contains a cyclic olefin polymer, and the manufacturing method includes a raw material film manufacturing step and a processing step.
[0015] The aforementioned raw material film manufacturing process comprises at least the following steps: a step of casting the coating material onto a support at a conveying speed V1 to form a wet film; a step of stretching the wet film in a first stage relative to the width of the freshly cast wet film; and a step of winding the film formed by drying the wet film.
[0016] The above processing steps include conveying the wound film at a conveying speed V2 to meet the following formula (1) and performing a second-stage stretching.
[0017] Equation (1): V1 < V2
[0018] Furthermore, in the process of stretching the wound film in the second stage described above, the winding width is stretched within the range of 0.1 to 0.5% by mass of residual solvent before the second stage stretching is to be performed.
[0019] 2. The method for manufacturing the polarizing protective film according to claim 1, characterized in that the residual solvent content before the first stage of stretching is in the range of 1 to 15% by mass, and the stretching ratio is in the range of 1.1 to 2.0 times.
[0020] 3. The method for manufacturing a polarizing protective film according to claim 1 or 2, characterized in that the stretching ratio in the second stage stretching process described above is in the range of 1.1 to 2.0 times.
[0021] According to the method described above, a method for manufacturing a polarizer protective film containing a cyclic olefin polymer with improved adhesion to polyvinyl alcohol-based films can be provided.
[0022] The mechanism of action or expression of the effects of this invention is not yet clear, but it is speculated as follows.
[0023] In this invention, the surface condition of the film can be improved by controlling the relative relationship of the film conveying speed in the raw material film manufacturing process and the processing process, as well as the amount of residual solvent in the film during stretching, within a certain range.
[0024] That is, it is speculated that: firstly, in the raw material film manufacturing process, by performing the first stage stretching in a state where a considerable amount of solvent remains in the film (wet film), the orientation of polymer constituent molecules in the film, such as polymer molecular chains, is biased towards the surface direction and forms a high-density layer, thereby enabling the physicochemical state of the surface to be suitable for improving adhesion.
[0025] In addition, it is speculated that by controlling the relative relationship of the membrane conveying speed in the raw material membrane manufacturing process and the processing process in a manner that satisfies the above formula (1), the residual solvent can be diffused during the stretching in the second stage, suppressing the formation of a high-density layer due to heat treatment. By adjusting the amount of residual solvent to below a certain amount, the amount of adhesive permeating into the membrane can be prevented from becoming excessive, thus avoiding the deterioration of the membrane strength.
[0026] It should be noted that by controlling the conveying speed and the amount of residual solvent during the second-stage stretching, it is possible to manufacture stretch films without deteriorating their adhesiveness.
[0027] The reason is believed to be that when the film is further stretched in the second stage with a residual solvent content of 0.1 to 0.5% by mass, the residual solvent diffuses during the stretching process under the condition that equation (1) is satisfied, thus suppressing the formation of the high-density layer caused by heat treatment.
[0028] On the other hand, it is believed that if equation (1) is not satisfied, that is, if the membrane transfer speed V2 is slower than V1, the internal solvent will evaporate into the stretching process, and the surface layer will become high-density due to the heat treatment of the additional stretching process. Attached Figure Description
[0029] Figure 1 This is a flowchart illustrating the manufacturing process of the present invention.
[0030] Figure 2 This is a simplified diagram of an apparatus for manufacturing protective films for polarizers. Detailed Implementation
[0031] The method for manufacturing the polarizing protective film of the present invention is characterized in that: the polarizing protective film contains a cyclic olefin polymer, the manufacturing method includes a raw material film manufacturing step and a processing step, the raw material film manufacturing step comprising at least a step of casting a coating onto a support at a conveying speed V1 to form a wet film, a step of stretching the wet film in a first stage relative to the width of the freshly cast wet film, and a step of winding the film formed by drying the wet film, the processing step comprising a step of conveying the wound film at a conveying speed V2 satisfying the following formula (1) and stretching it in a second stage.
[0032] Equation (1): V1 < V2
[0033] Furthermore, in the process of stretching the wound film in the second stage described above, the winding width is stretched within the range of 0.1 to 0.5% by mass of residual solvent before the second stage stretching is to be performed.
[0034] This feature is a common or corresponding technical feature of the following embodiments (morphologies).
[0035] As an embodiment of the present invention, from the viewpoint of improving the adhesion of the membrane and suppressing the deterioration of the membrane strength, it is preferable that the amount of residual solvent before the first stage of stretching described above is in the range of 1 to 15% by mass, and the stretching ratio is in the range of 1.1 to 2.0 times.
[0036] Furthermore, from the viewpoint of performance effect, it is more preferable that the stretching ratio in the above-mentioned second stage stretching process is in the range of 1.1 to 2.0 times.
[0037] The present invention, its constituent elements, and the forms and methods for carrying out the invention will be described in detail below. It should be noted that in this application, "~" is used to encompass the numerical values described before and after it as lower and upper limits.
[0038] [Manufacturing method of polarizing protective film]
[0039] The method for manufacturing the polarizing protective film of the present invention is characterized in that: the polarizing protective film contains a cyclic olefin polymer, the manufacturing method includes a raw material film manufacturing step and a processing step, the raw material film manufacturing step comprising at least a step of casting a coating onto a support at a conveying speed V1 to form a wet film, a step of stretching the wet film in a first stage relative to the width of the freshly cast wet film, and a step of winding the film formed by drying the wet film, the processing step comprising a step of conveying the wound film at a conveying speed V2 satisfying the following formula (1) and stretching it in a second stage.
[0040] Equation (1): V1 < V2
[0041] Furthermore, in the process of stretching the wound film in the second stage described above, the winding width is stretched within the range of 0.1 to 0.5% by mass of residual solvent before the second stage stretching is to be performed.
[0042] The following is for reference Figure 1 and Figure 2 The process steps of the manufacturing method using solution casting film formation are described.
[0043] Figure 1 This is a flowchart illustrating the manufacturing process of the present invention. Figure 2 This is a simplified diagram of an apparatus for manufacturing protective films for polarizers.
[0044] 1. Raw material membrane manufacturing process
[0045] The raw material film of the present invention is a film manufactured by solution casting film forming method. The raw material film manufacturing process consists of at least a process of casting coating material to a support at a conveying speed V1 to form a wet film, a process of stretching the wet film in the first stage relative to the width of the wet film after casting, and a process of winding the film formed by drying the wet film.
[0046] (1.1) The process of casting the coating onto the support at a conveying speed V1 to form a wet film.
[0047] The process described above, in which the coating is cast onto the support at a conveying speed V1 to form a wet film, consists of at least a coating preparation process (S1), a casting process (S2), and a peeling process (S3).
[0048] (1.1.1) Coating preparation (stirring preparation) process (S1)
[0049] In the coating preparation (stirring preparation) step (S1), at least the resin and solvent are stirred in the stirring tank 1a of the stirring device 1 to prepare the coating that is cast onto the support 3 (annular belt).
[0050] Hereinafter, as an embodiment of the present invention, the coating preparation process will be described as an example using a cyclic olefin polymer (hereinafter also referred to as "COP") as a thermoplastic resin.
[0051] This process involves dissolving the COP, along with other compounds used as appropriate, in a solvent, primarily a good solvent for cyclic olefin polymers (COP), in a dissolving vessel while stirring to form a coating, or mixing other compound solutions into the COP solution as appropriate to form a coating that serves as the main solvent.
[0052] (Concentration of cyclic olefin polymers)
[0053] A high concentration of cyclic olefin polymers (COPs) in the coating can reduce the drying load after casting onto the support, which is therefore preferred.
[0054] However, if the COP concentration is too high, the filtration load increases and the accuracy decreases.
[0055] As a concentration that balances both factors, a range of 10 to 35% by mass is preferred, and a range of 15 to 30% by mass is even more preferred.
[0056] (The solvent used in coatings)
[0057] The solvents used in coatings can be used alone or in combination of two or more. In terms of production efficiency, it is preferable to use a mixture of good solvents and poor solvents for cyclic olefin polymers (COPs). In terms of COP solubility, it is preferable to use more good solvents.
[0058] The preferred range for the mixing ratio of good solvent to poor solvent is 70-98% by mass of good solvent and 2-30% by mass of poor solvent.
[0059] In this specification, the terms "good solvent" and "poor solvent" refer to solvents used to dissolve cyclic olefin polymers (COPs) on their own, and solvents used to swell or not dissolve cyclic olefin polymers (COPs) on their own, which are defined as poor solvents. Therefore, whether a COP is a good or poor solvent may vary depending on the type and number of substituents in the COP.
[0060] The good solvents used in this invention are not particularly limited, and examples include organic halides such as dichloromethane, dioxolane, acetone, methyl acetate, methyl acetoacetate, etc.
[0061] Dichloromethane or methyl acetate are particularly preferred examples.
[0062] Furthermore, the lean solvent used in this invention is not particularly limited; for example, methanol, ethanol, n-butanol, cyclohexane, cyclohexanone, etc. are preferred.
[0063] In addition, the coating preferably contains 0.01 to 2.00% by mass of water.
[0064] In addition, the solvent used to dissolve cyclic olefin polymers (COP) is recycled and dried from the film during the polarizer protective film manufacturing process, and then reused.
[0065] The recycled solvent may sometimes contain trace amounts of additives added to COP, such as plasticizers, UV absorbers, polymers, monomers, etc., but even if they are present, they can be reused, or purified and reused if necessary.
[0066] The general method can be used as the method for dissolving COP in the preparation of coatings as described above.
[0067] Specifically, preferred methods include those performed at atmospheric pressure, those performed below the boiling point of the main solvent, and those performed under pressure above the boiling point of the main solvent. If heating and pressure are combined, heating can be performed above the boiling point at atmospheric pressure.
[0068] In addition, in order to prevent the formation of gel-like, undissolved lumps called condensates (mamako), it is preferable to dissolve the solvent by heating and stirring at a temperature above the boiling point of the solvent under normal pressure and within the range where the solvent does not boil under pressure.
[0069] Alternatively, a preferred method is to wet or swell the cyclic olefin polymer (COP) with a poor solvent and then dissolve it by adding a good solvent.
[0070] Pressurization can be achieved by injecting inactive gases such as nitrogen or by heating the solvent to increase its vapor pressure.
[0071] Heating is preferably performed externally; for example, jacketed heating devices are preferred because they are easier to control the temperature.
[0072] From the perspective of the solubility of cyclic olefin polymers (COP), a higher heating temperature is preferred after adding solvent. However, if the heating temperature is too high, the required pressure will increase and the productivity will decrease.
[0073] The preferred heating temperature is in the range of 30 to 120°C, more preferably in the range of 60 to 110°C, and even more preferably in the range of 70 to 105°C.
[0074] In addition, adjusting the pressure is used to prevent the solvent from boiling at the set temperature.
[0075] Alternatively, a cooling dissolution method is preferred, which allows cyclic olefin polymers (COPs) to dissolve in solvents such as methyl acetate.
[0076] (filter)
[0077] Next, the cyclic olefin polymer (COP) solution (the coating in or after dissolution) is preferably filtered using a suitable filter material such as filter paper.
[0078] As a filter material, the smaller the absolute filtration precision, the better in order to remove insoluble substances. If the absolute filtration precision is too small, the filter material is prone to clogging.
[0079] Therefore, filter media with an absolute filtration accuracy of less than 0.008 mm are preferred, filter media in the range of 0.001 to 0.008 mm are more preferred, and filter media in the range of 0.003 to 0.006 mm are even more preferred.
[0080] There are no particular restrictions on the material of the filter media; common filter media can be used. However, since there is no issue with fiber shedding, plastic filter media such as polypropylene and Teflon (registered trademark) or metal filter media such as stainless steel are preferred.
[0081] It is preferable to remove or reduce impurities, especially bright spots, in the raw material cyclic olefin polymer (COP) through filtration.
[0082] A bright spot (foreign object) refers to a point (foreign object) visible when light is shone from one side of one polarizer and observed from the other side, caused by light leakage from the opposite side when two polarizers are arranged in an orthogonal Nicol configuration with a film or similar material placed between them. Preferably, the number of bright spots with a diameter of 0.01 mm or more is 200 per cm. 2 the following.
[0083] More preferably 100 pieces / cm 2 The following is a further preferred value: 50 pieces / cm 2 The following is a further preferred value: 10 pieces / cm 2 the following.
[0084] In addition, the fewer bright spots smaller than 0.01mm, the better.
[0085] The filtration of coatings can be carried out using conventional methods. Since the increase in the pressure difference (called differential pressure) before and after filtration is small, it is preferable to use a method of heating and filtering at a temperature above the boiling point of the solvent under normal pressure and within the range where the solvent does not boil under pressure.
[0086] The preferred temperature range is 30–120°C, more preferably 45–70°C, and even more preferably 45–55°C.
[0087] The lower the filtration pressure, the better.
[0088] Specifically, it is preferably 1.6 MPa or less, more preferably 1.2 MPa or less, and even more preferably 1.0 MPa or less.
[0089] (1.1.2) Casting process (S2)
[0090] In the casting process (S2), the wet film 5 formed by the coating material cast onto the support 3 at a conveying speed V1 is heated on the support 3 to evaporate the solvent until the wet film 5 can be peeled off from the support 3 using the peeling roller 4.
[0091] Then, the amount of residual solvent before the first stage of stretching is controlled by evaporating the solvent.
[0092] The evaporation described above is preferably carried out in an atmosphere within the range of 5 to 75°C.
[0093] To evaporate the solvent, there are methods such as blowing warm air onto the upper surface of the wet film and / or conducting heat through the liquid from the back of the support 3, and conducting heat from the surface and back through radiant heat. Since the drying efficiency is good, the method of conducting heat from the surface and back through radiant heat is preferred.
[0094] Alternatively, it is preferable to use a method that combines them.
[0095] From a productivity point of view, the width of the cast is preferably 1.3m or more.
[0096] More preferably, it is in the range of 1.3 to 4.0 m.
[0097] If the width of the cast does not exceed 4.0m, no stripes are introduced in the manufacturing process, and the stability in the subsequent transfer process is increased.
[0098] From the perspective of transportability and productivity, a range of 1.3 to 3.0 m is further preferred.
[0099] In the casting process (S2), the support 3 preferably has a mirror-finished surface. As the support 3, a stainless steel strip or a casting with a plated and finished roller is preferably used.
[0100] In the casting process (S2), the surface temperature of the support 3 is within the range of -50°C to the boiling point of the solvent. The higher the temperature, the faster the wet film can dry, which is therefore preferred.
[0101] The preferred support temperature is within the range of 0 to 55°C, and more preferably within the range of 22 to 50°C.
[0102] There are no particular restrictions on the method of controlling the temperature of the support body 3. Methods include blowing warm or cold air, and making warm water come into contact with the back side of the support body.
[0103] Using warm water allows for efficient heat transfer, resulting in a shorter time for the support to reach a constant temperature, which is therefore preferable.
[0104] When using heating, sometimes the air temperature is higher than the target temperature.
[0105] In the casting process (S2), the coating prepared in the coating preparation process (S1) is sent to the casting die 2 through a conduit via a pressurized quantitative gear pump or the like. The casting die 2 then casts the coating onto the casting position on the support body 3, which is made of an infinitely moving, rotating stainless steel annular belt.
[0106] Here, the position where the coating flows out of the slit of the casting die is called the die lip. The shape of the slit in the die lip can be adjusted, and casting dies that make it easy to make the film thickness uniform are preferred.
[0107] Casting molds include hanger molds and T-shaped molds, all of which are preferred.
[0108] It should be noted that in this invention, "wet film" refers to the coating film cast from the aforementioned mold lip portion.
[0109] To increase the film-forming speed of the raw material film, two or more of the above-mentioned casting dies can be set on the support to divide the coating amount and form multiple layers.
[0110] Alternatively, a co-casting method in which multiple coatings are simultaneously cast can be preferred to obtain a laminated raw material film.
[0111] The slit can be narrowed by manually rotating and pressing in a heated bolt (ヒートボルト), thus thinning the film, or conversely, opened to thicken the film.
[0112] The method of pressing in the bolt by applying voltage to the heated bolt using heat is also common, but it is usually used in combination.
[0113] Alternatively, a pushing or pulling method can be used.
[0114] However, the bolt spacing in the casting die sometimes cannot be narrowed. In the case of high viscosity coatings (including melts), the pressure load on the die lip is large when the casting die is discharged, and the load decreases sharply after discharge, causing the film thickness to increase (balance effect). Such a width can sometimes cause deviations in film thickness.
[0115] Therefore, a design is needed that avoids applying excessive load to the die lip of the casting die through its internal structure.
[0116] In the casting process (S2), the coating material cast at a conveying speed V1 is dried on the support 3 to form a wet film 5.
[0117] At this time, the tilt of the casting die 2, that is, the discharge direction of the coating from the casting die 2 to the support 3, can be appropriately set within the range of 0 to 90° relative to the normal of the surface of the support 3 (the surface of the casting coating).
[0118] The support 3 is made of, for example, a stainless steel strip and is held by a pair of rollers 3a, 3b and a plurality of rollers located between them.
[0119] In this case, it is preferable that the surface of the support is a mirror.
[0120] One or both of the rollers 3a and 3b are provided with a drive device that applies tension to the support 3, thereby using the support 3 in a state where it is tensioned.
[0121] It should be noted that support 3 can also be a roller.
[0122] (1.1.3) Stripping process (S3)
[0123] In this process, the solvent is evaporated on the support 3 in the casting process (S2) until the wet film 5 becomes a peelable film strength. After drying and curing or cooling and solidification, the wet film is peeled off from the support 3 before the raw material film is wrapped around the support 3 once.
[0124] That is, this process is to peel off the wet film formed by solvent evaporation on the support 3 at the peeling position.
[0125] At this point, from the perspective of surface quality, moisture permeability, and peelability, it is preferable to peel the raw material film from the support within the range of 30 to 600 seconds.
[0126] It should be noted that the location where the wet film will be peeled off from the support is called the peeling point, and the roller that assists in peeling is called the peeling roller.
[0127] In the peeling process (S3), the wet film is peeled off using the peeling roller 4 while it is in a self-supporting state.
[0128] The temperature at the peeling point on the support is preferably in the range of -50 to 40°C, more preferably in the range of 10 to 40°C, and most preferably in the range of 15 to 30°C.
[0129] (Residual solvent content)
[0130] The amount of residual solvent before the first stage of stretching is adjusted appropriately by the strength of the drying conditions and the length of the support 3.
[0131] While it also depends on the thickness of the wet film, if there is too much residual solvent at the peel point, the wet film becomes too soft and difficult to peel off, which may sometimes impair flatness or cause horizontal lines, adhesion, or vertical lines due to peeling tension.
[0132] Conversely, if the amount of residual solvent is too small, sometimes a portion of the wet film will peel off midway.
[0133] In order to ensure that the wet film exhibits good planarity, from the perspective of balancing economy, speed and quality, the residual solvent content is preferably in the range of 1 to 50% by mass.
[0134] Furthermore, from the viewpoint of demonstrating the effects of the present invention, the preferred range is 1 to 15% by mass.
[0135] As a method to increase film-forming speed (because peeling is performed with as much residual solvent as possible, film-forming speed can be increased), there is gel casting (gel casting) which can peel off even with a large amount of residual solvent.
[0136] Methods include adding a solvent-poor cyclic olefin polymer (COP) to the coating and gelling the wet film after the coating is cast, and methods that gelle the wet film by cooling the support and peeling it off in a state containing a lot of residual solvent.
[0137] Alternatively, there is a method of adding metal salts to the coating.
[0138] As described above, by gelling the wet film on the support and strengthening the film, peeling can be accelerated and the film-making speed can be increased.
[0139] It should be noted that the amount of residual solvent is defined by the following formula.
[0140] Residual solvent content (mass%) = {(M - N) / N} × 100
[0141] It should be noted that M is the mass of the sample taken at any time during or after the manufacturing of the wet film or polarizing protective film, and N is the mass of M after heating it at 115°C for 1 hour.
[0142] (Method for determining residual solvent content)
[0143] The amount of residual solvent can be determined by headspace gas chromatography.
[0144] In headspace gas chromatography, the sample is sealed in a container and heated. While the container is filled with volatile components, the gas in the container is rapidly injected into the gas chromatograph. Mass analysis and identification of compounds are performed simultaneously, and the volatile components are quantified.
[0145] In headspace analysis, the total peak of volatile components can be observed using a gas chromatograph, and volatile substances, monomers, etc., can also be quantified with high precision by using analytical methods that utilize electromagnetic interactions.
[0146] (peel tension)
[0147] The peel tension when separating the support from the wet film is preferably below 300 N / m.
[0148] More preferably, the tension is in the range of 196 to 245 N / m. If wrinkles are easily generated during peeling, it is preferable to peel with a tension of 190 N / m or less.
[0149] (1.2) The process of stretching the wet film in the first stage relative to the width of the wet film immediately after casting.
[0150] This process is the first stage stretching process (S4), which is performed by stretching the wet film peeled from the support in the conveying direction (Machine Direction, hereinafter also referred to as "MD direction").
[0151] In this case, for the wet film, the contraction occurs within the wet film surface in the width direction (Traverse Direction, hereinafter also referred to as "TD direction") orthogonal to the MD direction.
[0152] Stretching can be performed according to the required optical properties, preferably in at least one direction, and can be performed in two mutually orthogonal directions (e.g., biaxial stretching in the width direction (TD direction) and the transport direction (MD direction) orthogonal to it of the film).
[0153] The stretch ratio is defined as (the magnitude of the stretch in the direction of the stretched film) / (the magnitude of the stretch in the direction of the film before stretching).
[0154] It should be noted that when performing biaxial stretching, the stretching ratio in the TD direction and MD direction is preferably set within the range of 1.1 to 2.0 times, respectively.
[0155] (Residual solvent content)
[0156] The amount of residual solvent before the first stage of stretching in this invention has the same meaning as the amount of residual solvent at the peeling point in the aforementioned peeling process (S3).
[0157] As an embodiment of the present invention, the residual solvent content before the first stage of stretching is in the range of 1 to 15% by mass, and from the viewpoint of improving the adhesion of the film and suppressing the deterioration of the film strength, the stretching ratio is preferably in the range of 1.1 to 2.0 times.
[0158] By performing the stretching process (S4) described above in the first stage, the entanglement between polymer molecules (matrix molecules) in the thickness direction of the wet film is promoted. As a result, even when the polarizer protective film is bonded to the polarizer layer by an adhesive during the fabrication of the polarizer, the adhesive can easily penetrate into the interior of the polarizer protective film through the entanglement between matrix molecules (cross-linking portion).
[0159] As a result, the polarizer protective film can be firmly fixed to the polarizer layer (also known as "polarizing film", "polarizer film" or "polarizer thin film") by an adhesive, which can improve the peel strength of the polarizer protective film to the polarizer layer.
[0160] In other words, it can improve the adhesion between the polarizer protective film and the polarizer layer, ensuring the function of suppressing the degradation of film strength.
[0161] In the first stage stretching process (S4) described above, the wet film is shrunk in the width direction.
[0162] Methods for shrinking wet films include (1) subjecting the wet film to high-temperature treatment without maintaining its width to increase the density of the wet film, (2) applying tension to the wet film in the transport direction (MD direction) to shrink the wet film in the width direction (TD direction), and (3) drastically reducing the amount of residual solvent in the wet film.
[0163] (1.3) The process of winding the film formed by drying the wet film.
[0164] This process consists of a drying process (S5), a first cutting process (S6), and a first winding process (S7).
[0165] It should be noted that the coating conveying speed V1 in the coating preparation process (S1) and the winding speed in the first winding process (S7) are the same.
[0166] In addition, the phrase "the conveying speed and the winding speed are the same" in the above context strictly means that they are the same within a range of ±10%.
[0167] (1.3.1) Drying process (S5)
[0168] The drying process (S5) is a process in which the wet film is heated on a support to evaporate the solvent and the resulting film is wound up.
[0169] Figure 2 In the drying device 7, multiple conveying rollers arranged in a serrated shape when viewed from the side are used to convey the wet film and dry it in the process.
[0170] There are no particular restrictions on the drying method in the drying device 7. Generally, hot air, infrared rays, heating rollers, microwaves, etc. are used to dry the wet film. From the perspective of simplicity, the method of using hot air to dry the wet film is preferred.
[0171] Alternatively, combining them is also preferred.
[0172] It should be noted that the drying process (S5) can be performed only as needed.
[0173] The thinner the wet film, the faster it dries; however, excessively rapid drying can damage the flatness of the finished film.
[0174] When using high temperature for drying, the amount of residual solvent needs to be considered. By ensuring that the amount of residual solvent is not too large, malfunctions caused by solvent foaming can be prevented.
[0175] Throughout the process, the drying is carried out in the range of approximately 30 to 250°C.
[0176] It is particularly preferred to dry in the range of 35 to 200°C, and it is even more preferable to increase the drying temperature in stages.
[0177] The temperature of the support structure can be uniform throughout, or it can vary depending on its location.
[0178] In the drying process of wet film, roller drying (a method in which the wet film is dried by alternately passing through multiple rollers arranged above and below) and stretching method are generally used to convey and dry the wet film at the same time.
[0179] When using a tensioning device, it is preferable to use a device that allows the left and right holding mechanisms of the tensioning device to independently control the holding length (distance from the start of holding to the end of holding) of the wet film in the stretching process described later.
[0180] (1.3.2) First cutting process (S6)
[0181] In the first cutting process (S6), the cutting section 8, which is composed of a slitter, cuts the two ends of the film F in the width direction, which has been stretched in the first stage stretching process (S4) and has passed through the drying process (S5).
[0182] In membrane F, the remaining portions after the two ends are cut off constitute the product portion as a membrane product.
[0183] On the other hand, the portion cut off from membrane F can be recycled and reused again as part of the raw materials in the production of polarizing protective films.
[0184] (1.3.3) First winding process (S7)
[0185] In the first winding process (S7), the film F is wound by the winding device 9 at a conveying speed V1 (winding speed V1), and the raw material film manufacturing process ends.
[0186] The preferred range for the initial tension during the winding process of film F is 20–300 N / m.
[0187] 2. Processing steps
[0188] The processing step is a process in which the above-mentioned film to be wound is conveyed through the process of being pulled out of its roll (S8) at a conveying speed V2 satisfying the following formula (1) and subjected to a second stage stretching, and is composed of at least the extraction process (S8), the second stage stretching stroke (S9), the second cutting process (S10) and the second winding process (S11).
[0189] Equation (1) V1 < V2
[0190] (Residual solvent content)
[0191] In the manufacturing method of the present invention, the amount of residual solvent before the second stage of stretching is in the range of 0.1% to 0.5% by mass.
[0192] (2.1) Second stage stretching process (S9)
[0193] The second stage stretching process (S9) can be a process that stretches the membrane in the membrane surface only in the MD direction, or a process that stretches only in the TD direction, or a process that stretches in both the MD and TD directions, or a process that stretches in an inclined direction.
[0194] Furthermore, there is no limitation on the stretching direction, but from the viewpoint of obtaining a wide film, it is preferable to have at least a process that includes stretching in the width direction.
[0195] Such stretching can be performed using the stretching device 10.
[0196] To ensure a high phase difference, a wide width, and to promote adhesive penetration during bonding with the polarizing film, it is preferable to stretch the film at a high ratio in the second-stage stretching process.
[0197] However, if the stretching ratio is too high, tensile stress may cause cracks in the membrane or dissociate the entanglement between matrix molecules that maintain the membrane strength, thus weakening the membrane.
[0198] Therefore, from the viewpoint of demonstrating the effect of the present invention, it is more preferable that the stretching ratio in the second stage stretching process is in the range of 1.1 to 2.0 times.
[0199] It should be noted that, as in this invention, when multiple stretching processes are performed, such as stretching after the peeling process and stretching during the second stage stretching stroke, the stretching at the highest ratio with the highest risk of matrix molecule dissociation is preferably performed in the last stretch.
[0200] Therefore, in this invention, it is preferable to perform the stretching at the highest ratio during the second stage of the stretching stroke.
[0201] In this case, since the matrix molecules can be firmly entangled up to the highest stretching ratio, the dissociation of the matrix molecules can be suppressed even when the stretching ratio is the highest, thus suppressing the destruction of the entanglement.
[0202] In the second stage stretching process (S9), the film F is stretched using the stretching device 10.
[0203] As a stretching method at this time, in order to improve the performance, productivity, flatness, and dimensional stability of the film, it is preferable to set the circumferential speed difference of the roller to stretch in the conveying direction (the long side direction of the film; the film forming direction; the casting direction; the MD direction) or to fix the two sides of the film with clamps or the like and stretch in the width direction (the orthogonal direction in the film surface; the TD direction).
[0204] In addition, when using the so-called stretching method, if the clamp part is driven in a linear drive manner, smooth stretching can be achieved, which can reduce the risk of breakage, and is therefore preferred.
[0205] These width-maintaining or lateral stretching processes in the film-making process are preferably performed using a tenter frame, such as a pin-plate tenter frame or a clamp tenter frame.
[0206] It should be noted that drying can also be performed inside the stretching device 10 in addition to stretching.
[0207] (2.2) Second cutting process (S10)
[0208] In the second cutting process (S10), the cutting section 11, which is composed of a slitting mechanism, cuts off both ends of the film F in the width direction that has been stretched by the second stage stretching process (S9).
[0209] In membrane F, the remaining portions after the two ends are cut off constitute the product portion as a membrane product.
[0210] On the other hand, the portion cut off from membrane F can be recycled and reused again as part of the raw materials in membrane manufacturing.
[0211] (2.3) Second winding process (S11)
[0212] In the second winding process (S11), the film F is wound by the winding device 12 at a conveying speed V2.
[0213] It should be noted that, at this time, the thickness of the membrane is preferably in the range of 5 to 100 μm, more preferably in the range of 5 to 80 μm, and even more preferably in the range of 5 to 40 μm.
[0214] The preferred range for the initial tension during the winding of film F in the second winding process (S11) is 20 to 300 N / m.
[0215] (Winding method)
[0216] The winding method for membrane F can be achieved using a commonly used winding machine. There are various tension control methods, such as constant torque method, constant tension method, conical tension method, and programmed tension control method with certain internal stress. These methods can be used separately.
[0217] Before winding, the ends are cut off along the width of the finished product. To prevent sticking or scratching during winding, the ends of the film can be surface modified.
[0218] 3. Types of polymers
[0219] The polymer (resin) used in the manufacturing method of the polarizing protective film of the present invention is a cyclic olefin polymer (also known as "cyclic olefin resin"), which is superior to other thermoplastic polymers (resins) in terms of easy control of stretchability and crystallinity, as well as easy penetration of adhesives and the ability to ensure better adhesion to the polarizing film.
[0220] It should be noted that the aforementioned polarizer protective film can also undergo surface modification treatment after manufacturing.
[0221] (Cyclic olefin polymers)
[0222] The cyclic olefin polymer contained in the polarizer protective film is preferably a polymer of cyclic olefin monomers or a copolymer of cyclic olefin monomers and other comonomers.
[0223] As a cyclic olefin monomer, a cyclic olefin monomer having a norbornene skeleton is preferred, and a cyclic olefin monomer having a structure represented by the following general formula (A-1) or (A-2) is more preferred.
[0224]
[0225] In general formula (A-1), R 1 ~R 4 Each can independently represent a hydrogen atom, a hydrocarbon group with 1 to 30 carbon atoms, or a polar group. p represents an integer from 0 to 2. Where R... 1 ~R 4 Not all of them simultaneously represent hydrogen atoms, R 1 and R 2 R does not simultaneously represent hydrogen atoms 3 and R 4 They do not both represent hydrogen atoms.
[0226] As R in general formula (A-1) 1 ~R 4 The hydrocarbon group representing 1 to 30 carbon atoms is preferably a hydrocarbon group representing 1 to 10 carbon atoms, and more preferably a hydrocarbon group representing 1 to 5 carbon atoms.
[0227] The hydrocarbon group having 1 to 30 carbon atoms may further have a linking group containing halogen atoms, oxygen atoms, nitrogen atoms, sulfur atoms or silicon atoms.
[0228] Examples of such linking groups include divalent polar groups such as carbonyl, imino, ether, silyl ether, and thioether.
[0229] Examples of hydrocarbon groups with 1 to 30 carbon atoms include methyl, ethyl, propyl, and butyl.
[0230] In general formula (A-1), R 1 ~R 4 Examples of polar groups include carboxyl, hydroxyl, alkoxy, alkoxycarbonyl, aryloxycarbonyl, amino, amide, and cyano.
[0231] Among them, carboxyl, hydroxy, alkoxycarbonyl and aryloxycarbonyl are preferred. From the viewpoint of ensuring solubility during solution film formation, alkoxycarbonyl and aryloxycarbonyl are preferred.
[0232] From the perspective of improving the heat resistance of the polarizer protective film, p in the general formula (A-1) is preferably 1 or 2.
[0233] This is because when p is 1 or 2, the polymer volume increases, making it easier to increase the glass transition temperature.
[0234]
[0235] In general formula (A-2), R 5 R represents a hydrogen atom, a hydrocarbon group having 1 to 5 carbon atoms, or an alkylsilyl group having 1 to 5 carbon atoms. 6 This indicates a carboxyl, hydroxyl, alkoxycarbonyl, aryloxycarbonyl, amino, amide, cyano, or halogen atom (fluorine, chlorine, bromine, or iodine). p represents an integer from 0 to 2.
[0236] R in general formula (A-2) 5 Preferably, the hydrocarbon group represents 1 to 5 carbon atoms, and more preferably, the hydrocarbon group represents 1 to 3 carbon atoms.
[0237] R in general formula (A-2) 6 The preferred groups are carboxyl, hydroxyl, alkoxycarbonyl, and aryloxycarbonyl. From the viewpoint of ensuring solubility during solution film formation, alkoxycarbonyl and aryloxycarbonyl are more preferred.
[0238] From the perspective of improving the heat resistance of the polarizer protective film, p in general formula (A-2) preferably represents 1 or 2.
[0239] This is because when p represents 1 or 2, the polymer volume increases, making it easier to increase the glass transition temperature.
[0240] From the perspective of improving solubility in organic solvents, cyclic olefin monomers having a structure represented by general formula (A-2) are preferred.
[0241] Generally, organic compounds reduce crystallinity by disrupting symmetry, thus increasing their solubility in organic solvents.
[0242] R in general formula (A-2) 5 and R 6 The symmetry of the molecule is low because it is substituted only on one side of the ring-forming carbon atom relative to the symmetry axis of the molecule. That is, the cycloolefin monomer with the structure represented by the general formula (A-2) has high solubility, making it suitable for manufacturing polarizing protective films by solution casting.
[0243] The proportion of cyclic olefin monomers having the structure represented by general formula (A-2) in the polymer of cyclic olefin monomers relative to the total of all cyclic olefin monomers constituting the cyclic olefin polymer can be, for example, 70 mol% or more, preferably 80 mol% or more, and more preferably 100 mol%.
[0244] If the polymer contains a certain amount or more of cyclic olefin monomers with a structure represented by the general formula (A-2), the orientation of the polymer is improved, and therefore the phase difference (retardation) value tends to increase.
[0245] Hereinafter, specific examples of cyclic olefin monomers having the structure represented by general formula (A-1) are shown in Examples 1 to 14, and specific examples of cyclic olefin monomers having the structure represented by general formula (A-2) are shown in Examples 15 to 34.
[0246]
[0247] Examples of comonomers that can copolymerize with cyclic olefin monomers include comonomers that can undergo ring-opening copolymerization with cyclic olefin monomers and comonomers that can undergo addition copolymerization with cyclic olefin monomers.
[0248] Examples of ring-opening copolymerizable comonomers include cycloolefins such as cyclobutene, cyclopentene, cycloheptene, cyclooctene, and dicyclopentadiene.
[0249] Examples of addition copolymerizable comonomers include compounds containing unsaturated double bonds, vinyl cyclic hydrocarbon monomers, and (meth)acrylates.
[0250] Examples of compounds containing unsaturated double bonds include olefinic compounds with 2 to 12 carbon atoms (preferably 2 to 8), such as ethylene, propylene, and butene.
[0251] Examples of vinyl cyclic hydrocarbon monomers include vinylcyclopentene monomers such as 4-vinylcyclopentene and 2-methyl-4-isopropenylcyclopentene.
[0252] Examples of (meth)acrylates include alkyl (meth)acrylates with 1 to 20 carbon atoms, such as methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate.
[0253] The proportion of cyclic olefin monomers in the copolymer of cyclic olefin monomers and copolymeric monomers relative to the total of all monomers constituting the copolymer can be, for example, in the range of 20 to 80 mol%, preferably in the range of 30 to 70 mol%.
[0254] As mentioned above, cyclic olefin polymers are polymers obtained by polymerizing or copolymerizing cyclic olefin monomers having a norbornene skeleton, preferably cyclic olefin monomers having a structure represented by general formula (A-1) or (A-2), and examples include the following polymers (1) to (7).
[0255] (1) Ring-opening polymers of cyclic olefin monomers
[0256] (2) Ring-opening copolymers of cyclic olefin monomers and comonomers that can undergo ring-opening copolymerization with them
[0257] (3) The hydride of the ring-opening (co)polymer of (1) or (2) above
[0258] (4) Hydrogenated (copolymer) formed by cyclizing the ring-opening (co)polymer of (1) or (2) above via Friedel-Crafts reaction.
[0259] (5) Saturated copolymers of cycloolefin monomers and compounds containing unsaturated double bonds
[0260] (6) Addition copolymers of cyclic olefin monomers and vinyl cyclic hydrocarbon monomers and their hydrides
[0261] (7) Alternating copolymers of cyclic olefin monomers and (meth)acrylates
[0262] The polymers mentioned in (1) to (7) can all be obtained by known methods, such as those described in Japanese Patent Application Publication No. 2008-107534 and Japanese Patent Application Publication No. 2005-227606.
[0263] For example, the catalyst and solvent used in the ring-opening copolymerization in (2) above can be those described in paragraphs 0019 to 0024 of Japanese Patent Application Publication No. 2008-107534.
[0264] The catalysts used in the hydrides of (3) and (6) above may, for example, be the catalysts described in paragraphs 0025 to 0028 of Japanese Patent Application Publication No. 2008-107534.
[0265] The acidic compound used in the Friedel-Crafts reaction described in (4) above can be, for example, the acidic compound described in paragraph 0029 of Japanese Patent Application Publication No. 2008-107534.
[0266] The catalyst used in the addition polymerization of (5) to (7) above can be, for example, the catalyst described in paragraphs 0058 to 0063 of Japanese Patent Application Publication No. 2005-227606.
[0267] The alternating copolymerization reaction described in (7) above can be carried out, for example, by the method described in paragraphs 0071 and 0072 of Japanese Patent Application Publication No. 2005-227606.
[0268] Among them, the polymers of (1) to (3) and (5) above are preferred, and the polymers of (3) and (5) above are more preferred.
[0269] That is, in terms of increasing the glass transition temperature and light transmittance of the obtained cyclic olefin polymer, the cyclic olefin polymer preferably contains at least one of the structural units represented by the following general formula (B-1) and the following general formula (B-2), more preferably it contains only the structural unit represented by general formula (B-2), or it contains both the structural units represented by general formula (B-1) and the structural units represented by general formula (B-2).
[0270] The structural unit represented by general formula (B-1) is a structural unit derived from the cyclic olefin monomer represented by the aforementioned general formula (A-1), and the structural unit represented by general formula (B-2) is a structural unit derived from the cyclic olefin monomer represented by the aforementioned general formula (A-2).
[0271]
[0272] In general formula (B-1), X represents -CH=CH- or -CH2CH2-. 1 ~R 4 And p are respectively related to R in general formula (A-1) 1 ~R 4 It has the same meaning as p.
[0273]
[0274] In general formula (B-2), X represents -CH=CH- or -CH2CH2-. 5 ~R 6 And p are respectively related to R in general formula (A-2)5 ~R 6 It has the same meaning as p.
[0275] The cyclic olefin polymers of the present invention can be commercially available products.
[0276] Examples of commercially available cyclic olefin polymers include Arton G (e.g., G7810), Arton F, Arton R (e.g., R4500, R4900 and R5000), and Arton RX manufactured by JSR Corporation.
[0277] The intrinsic viscosity [η]inh of cycloolefin polymers is preferably 0.2–5 cm⁻¹ when measured at 30°C. 3 The range of / g is more preferably 0.3 to 3 cm. 3 The range of / g is further preferably 0.4–1.5 cm. 3 The range of / g.
[0278] The number-average molecular weight (Mn) of the cyclic olefin polymer is preferably in the range of 8,000 to 100,000, more preferably in the range of 10,000 to 80,000, and even more preferably in the range of 12,000 to 50,000.
[0279] The weight-average molecular weight (Mw) of the cyclic olefin polymer is preferably in the range of 20,000 to 300,000, more preferably in the range of 30,000 to 250,000, and even more preferably in the range of 40,000 to 200,000.
[0280] The number-average molecular weight and weight-average molecular weight of cyclic olefin polymers can be determined by gel permeation chromatography (GPC) with polystyrene conversion.
[0281] (Gel permeation chromatography)
[0282] Solvent: dichloromethane
[0283] Columns: Shodex K806, K805, K803G (manufactured by Showa Denko Co., Ltd., for use with 3 columns)
[0284] Column temperature: 25℃
[0285] Sample concentration: 0.1% by mass
[0286] Detector: RI Model 504 (manufactured by GLSCIENCES)
[0287] Pump: L6000 (manufactured by Hitachi, Ltd.)
[0288] Flow rate: 1.0 mL / min
[0289] Standard curve: A standard curve based on 13 samples of standard polystyrene (STKstandard, manufactured by Tosoh Corporation) with a Mw range of 500 to 2,800,000 was used. The 13 samples were preferably used at almost equal intervals.
[0290] If the intrinsic viscosity [η]inh, number-average molecular weight, and weight-average molecular weight are within the above ranges, the heat resistance, water resistance, reagent resistance, mechanical properties, and processability as a film of the cyclic olefin polymer become good.
[0291] The glass transition temperature (Tg) of cycloolefin polymers is typically above 110°C, preferably in the range of 110–350°C, more preferably in the range of 120–250°C, and even more preferably in the range of 120–220°C.
[0292] If the glass transition temperature (Tg) is above 110℃, deformation under high temperature conditions can be easily suppressed.
[0293] On the other hand, if the glass transition temperature (Tg) is below 350°C, molding becomes easier and the degradation of the polymer (resin) caused by heat during molding is more easily suppressed.
[0294] The content of the cyclic olefin polymer relative to the membrane is preferably 70% by mass or more, and more preferably 80% by mass or more.
[0295] 4. Polarizing filter
[0296] The polarizer of the present invention has a polarizer layer, a polarizer protective film of the present invention, and an adhesive layer containing a water-based adhesive or a UV-curable adhesive disposed therebetween.
[0297] (4.1) Polarizer layer
[0298] The polarizer layer of the present invention is a layer composed of at least a polarizing film (also referred to as a "polarizer film" or "polarizer thin film").
[0299] Here, "polarizer" refers to a component that allows light from a polarized surface in a specific direction to pass through.
[0300] The polarizing film of the present invention is a polyvinyl alcohol-based polarizing film.
[0301] Polyvinyl alcohol polarizing films include polyvinyl alcohol polarizing films obtained by dyeing polyvinyl alcohol films with iodine, and polyvinyl alcohol polarizing films obtained by dyeing polyvinyl alcohol films with dichroic dyes.
[0302] The polyvinyl alcohol polarizing film can be a film obtained by uniaxially stretching a polyvinyl alcohol film and then dyeing it with iodine or dichroic dyes (preferably a film that has been further subjected to a durability treatment with boron compounds); or it can be a film obtained by uniaxially stretching a polyvinyl alcohol film after dyeing it with iodine or dichroic dyes (preferably a film that has been further subjected to a durability treatment with boron compounds).
[0303] The absorption axis of the polarizer layer is usually parallel to the direction of maximum tension.
[0304] For example, ethylene-modified polyvinyl alcohol with an ethylene unit content of 1 to 4 mol%, a degree of polymerization of 2000 to 4000, and a degree of saponification of 99.0 to 99.99 mol%, as described in Japanese Patent Application Publication No. 2003-248123 and Japanese Patent Application Publication No. 2003-342322, can be used.
[0305] The thickness of the polarizer layer is preferably 5 to 30 μm, and more preferably 5 to 20 μm in order to make the polarizer thinner.
[0306] (4.2) Polarizing protective film
[0307] The polarizer protective film manufactured by the method of the present invention is disposed on at least one side of the polarizer layer (at least the side opposite to the liquid crystal cell).
[0308] The surface of the polarizer layer of the polarizer protective film was subjected to the activation treatment described later.
[0309] When a polarizer protective film manufactured by the method of the present invention is disposed on only one side of the polarizer layer, an optical film such as a phase retardation film can be disposed on the other side of the polarizer layer.
[0310] Other examples of optical films include commercially available cellulose ester films (e.g., Konica Minolta TAC KC8UX, KC5UX, KC4UX, KC8UCR3, KC4SR, KC4BR, KC4CR, KC4DR, KC4FR, KC4KR, KC8UY, KC6UY, KC4UY, KC4UE, KC8UE, KC8UY-HA, KC2UA, KC4UA, KC6UA, KC8UA, KC2UAH, KC4UAH, KC6UAH, all manufactured by Konica Minolta Co., Ltd.); Fuji TAC T40UZ, Fuji TAC T60UZ, Fuji TAC T80UZ, Fuji TAC TD80UL, Fuji TAC TD60UL, Fuji TAC TD40UL, Fuji TAC R02, Fuji TAC...). R06, all of the above are manufactured by Fujifilm Corporation, etc.
[0311] The thickness of other optical films can be, for example, 5 to 100 μm, preferably 40 to 80 μm.
[0312] (4.3) Adhesive layer
[0313] The adhesive layer is formed by drying a water-based adhesive or a UV-curing adhesive, which is disposed between the optical film (or other optical film) and the polarizer layer.
[0314] The thickness of the adhesive layer can be, for example, 0.01 to 10 μm, preferably about 0.03 to 5 μm.
[0315] (4.4) Manufacturing method of polarizer
[0316] The method for manufacturing a polarizer of the present invention comprises: 1) a step of activating the surface of a polarizer protective film; 2) a step of laminating a polarizer layer (polarizing film) onto the activated surface of the polarizer protective film using a water-based adhesive or an ultraviolet-curable adhesive; and 3) a step of drying the resulting laminate.
[0317] 1) process
[0318] The surface of the polarizer protective film (the surface that is attached to the polarizer layer) is activated.
[0319] Therefore, it is easy to obtain adhesion to the polarizer layer.
[0320] Specifically, by activating the side chains of specific grafted polymers contained in the polarizer protective film, the siloxane bonds, ether bonds, tertiary carbon atoms, etc., are made hydrophilic, thereby increasing their affinity with water-based adhesives or making them more likely to interact with each other, thus making it easier for the polarizer protective film to bond with the polarizer layer.
[0321] Examples of activation treatments include corona treatment, plasma treatment, and saponification treatment, with corona treatment and plasma treatment being preferred, and corona treatment being more preferred.
[0322] The activation treatment conditions are only required to fully activate the siloxane bonds, ether bonds, tertiary carbon atoms, etc. contained in the side chains of the specific grafted polymer.
[0323] When the activation treatment is corona treatment, the irradiation dose is preferably 100–1000 (W·min / m²). 2 More preferably, it is 150–900 (W·min / m³). 2 ).
[0324] 2) process
[0325] Next, the polarizer layer is laminated onto the activated surface of the optical film using a water-based adhesive or a UV-curable adhesive.
[0326] (Water-based adhesive)
[0327] Examples of water-based adhesives include vinyl-based, gelatin-based, vinyl latex-based, polyurethane-based, isocyanate-based, polyester-based, and epoxy-based adhesives.
[0328] From the viewpoint of easily obtaining adhesion to the polyvinyl alcohol-based polarizing film used as the polarizer layer, an aqueous adhesive containing a vinyl polymer is preferred, and an aqueous adhesive containing a polyvinyl alcohol-based polymer (such as a fully saponified polyvinyl alcohol aqueous solution) is more preferred.
[0329] Aqueous adhesives containing polyvinyl alcohol polymers may further contain water-soluble crosslinking agents such as boric acid, borax, glutaraldehyde, melamine, and oxalic acid.
[0330] (UV-curing adhesive)
[0331] UV-curable adhesives can be photoradical polymers or photocationic polymers.
[0332] Among them, photocationically polymerizable compositions are preferred.
[0333] The photocationically polymerizable composition comprises an epoxy compound and a photocationically polymerizable initiator.
[0334] Epoxy compounds are compounds that have one or more, preferably two or more, epoxy groups in their molecules.
[0335] Examples of epoxy compounds include hydrogenated epoxy compounds (glycidyl ethers of polyols having an alicyclic ring) obtained by reacting epichlorohydrin with an alicyclic polyol; aliphatic epoxy compounds such as polyglycidyl ethers of aliphatic polyols or their olefinic adducts; and alicyclic epoxy compounds having one or more epoxy groups bonded to an alicyclic ring within the molecule.
[0336] Epoxy compounds can be used in combination with one or more.
[0337] Photocationic polymerization initiators can be, for example, aromatic diazonium salts; aromatic iodine. Salt, aromatic matte salts, etc. Salts; iron-aromatic complexes, etc.
[0338] Photocationic polymerization initiators can be further enriched with cationic polymerization promoters such as oxetane and polyols, photosensitizers, solvents, etc., as needed.
[0339] The thickness of the adhesive layer is not particularly limited, for example, it is 0.01 to 10 μm, and preferably about 0.01 to 5 μm.
[0340] 3) process
[0341] Next, the resulting laminate is dried to obtain a polarizer.
[0342] Drying can be achieved through heating.
[0343] The drying temperature can be any temperature at which water-based adhesives or UV-curing adhesives are fully dried, for example, 60 to 100°C.
[0344] 5. Other additives
[0345] In addition to the cyclic olefin polymer (COP) mentioned above, the manufacturing method of the polarizer protective film of the present invention may also contain the following additives as other additives.
[0346] (5.1) Plasticizers
[0347] The polarizing protective film preferably contains at least one plasticizer for the purpose of imparting processability to the polarizing protective film, etc.
[0348] Plasticizers are preferably used alone or in combination of two or more.
[0349] From the viewpoint of achieving both effective control of moisture permeability and compatibility with base polymers (resins) such as cellulose esters, it is preferable that the plasticizer contains at least one plasticizer selected from sugar esters, polyesters and styrene compounds.
[0350] From the viewpoint of improving both resistance to damp heat and compatibility with base polymers (resins) such as cellulose esters, the plasticizer is preferably a polymer with a molecular weight of 15,000 or less, and more preferably 10,000 or less.
[0351] When the compound with a molecular weight of 10,000 or less is a polymer, it is preferred that the weight-average molecular weight (Mw) is 10,000 or less.
[0352] The preferred range for weight-average molecular weight (Mw) is 100 to 10,000, and more preferably 400 to 8,000.
[0353] In particular, in order to obtain the effects of the present invention, it is preferable that the compound with a molecular weight of less than 1500 is contained in the range of 6 to 40 parts by mass relative to 100 parts by mass of the base polymer (resin), and more preferably in the range of 10 to 20 parts by mass.
[0354] It is preferred because it contains substances within the above-mentioned range that can effectively control moisture permeability and have compatibility with the substrate resin.
[0355] (glycoesters)
[0356] To prevent hydrolysis, glycoester compounds can be included in the polarizer protective film.
[0357] Specifically, as a sugar ester compound, a sugar ester obtained by esterification of at least one of a pyranose structure or a furanose structure having 1 to 12 hydroxyl groups, wherein all or part of the OH groups of the structure are used.
[0358] (Polyester)
[0359] Polarizing protective films can also contain polyester.
[0360] Polyesters are not particularly limited; for example, polymers with terminal hydroxyl groups (polyester polyols) that can be obtained by condensation reaction of dicarboxylic acids or their ester-forming derivatives with diols, or polymers whose terminal hydroxyl groups are blocked by monocarboxylic acids (terminated polyesters) can be used.
[0361] The ester-forming derivatives mentioned here refer to esters of dicarboxylic acids, acyl chlorides of dicarboxylic acids, and anhydrides of dicarboxylic acids.
[0362] (Styrene compounds)
[0363] In addition to or in place of the aforementioned sugar esters and polyesters, styrene-based compounds may also be used in polarizing protective films to improve their water resistance.
[0364] Styrene compounds can be homopolymers of styrene monomers or copolymers of styrene monomers with other comonomers.
[0365] In order to achieve a certain large volume in the molecular structure, the proportion of constituent units derived from styrene monomers in styrene compounds is preferably in the range of 30 to 100 mol%, and more preferably in the range of 50 to 100 mol%.
[0366] Examples of styrene monomers include styrene; alkyl-substituted styrene such as α-methylstyrene, β-methylstyrene, and p-methylstyrene; halogen-substituted styrene such as 4-chlorostyrene and 4-bromostyrene; hydroxystyrene such as p-hydroxystyrene, α-methyl-p-hydroxystyrene, 2-methyl-4-hydroxystyrene, and 3,4-dihydroxystyrene; vinyl benzyl alcohols; alkoxy-substituted styrene such as p-methoxystyrene, p-tert-butoxystyrene, and m-tert-butoxystyrene; vinyl benzoic acid such as 3-vinylbenzoic acid and 4-vinylbenzoic acid; 4-vinylbenzyl acetate; 4-acetoxystyrene; amide styrene such as 2-butamidostyrene, 4-formamidostyrene, and p-styrenesulfonamide; aminostyrene such as 3-aminostyrene, 4-aminostyrene, 2-isopropenylaniline, and vinylbenzyldimethylamine; nitrostyrene such as 3-nitrostyrene and 4-nitrostyrene; cyanostylstyrene such as 3-cyanostylstyrene and 4-cyanostylstyrene; vinyl styrene acetonitrile; aryl styrene such as phenylstyrene; and indene.
[0367] Styrene monomers can be one type or a combination of two or more types.
[0368] (5.2) Any component
[0369] Polarizing protective films can contain antioxidants, colorants, UV absorbers, matting agents, acrylic particles, hydrogen-bonded solvents, ionic surfactants, and any other ingredients.
[0370] These components can be added in the range of 0.01 to 20 parts by weight relative to 100 parts by weight of the base polymer (resin).
[0371] (Antioxidants)
[0372] Polarizing protective films can use commonly known antioxidants as antioxidants.
[0373] In particular, compounds of the lactone, sulfur, phenol, double bond, hindered amine, and phosphorus groups can be preferred.
[0374] These antioxidants are added in the range of 0.05 to 20% by mass, preferably in the range of 0.1 to 1% by mass, relative to the polymer (resin) that is the main raw material for the polarizer protective film.
[0375] These antioxidants, etc., can achieve synergistic effects by using a variety of different compounds in combination, compared to using only one.
[0376] For example, preferred combinations of lactone-based, phosphorus-based, phenolic, and double-bond-based compounds.
[0377] (Coloring agent)
[0378] To adjust the hue, the polarizing protective film preferably contains a colorant, within the scope of not impairing the effectiveness of the present invention.
[0379] Colorant refers to dyes and pigments. In this invention, it refers to a substance that has the effect of making the hue of the liquid crystal screen blue or adjusting the yellow index and reducing haze.
[0380] As a coloring agent, various dyes and pigments can be used, with anthraquinone dyes, azo dyes, phthalocyanine pigments, etc. being effective.
[0381] (UV absorber)
[0382] Polarizing protective films can also be used on the viewing side and backlight side of polarizing films, and therefore may contain ultraviolet absorbers to impart ultraviolet absorption function.
[0383] There are no particular limitations on what constitutes a UV absorber; for example, benzotriazole, 2-hydroxybenzophenone, or phenyl salicylate UV absorbers can be cited.
[0384] Examples include triazoles such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, and 2-(3,5-di-tert-butyl-2-hydroxyphenyl)benzotriazole, as well as benzophenones such as 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, and 2,2'-dihydroxy-4-methoxybenzophenone.
[0385] The aforementioned ultraviolet absorbers can be used alone or in combination of two or more.
[0386] The amount of ultraviolet absorber used varies depending on the type of ultraviolet absorber and the conditions of use. Generally, it is added in the range of 0.05% to 10% by mass relative to the substrate polymer (resin), preferably in the range of 0.1% to 5% by mass.
[0387] (particle)
[0388] The polarizer protective film preferably contains microparticles that impart lubricity to the polarizer protective film.
[0389] In particular, from the viewpoint of improving the lubricity of the polarizer protective film surface of the present invention, improving the lubricity during winding, and preventing the generation of scratches and blockages, the addition of microparticles is effective.
[0390] As for the microparticles, they can be either inorganic or organic microparticles, provided that they have heat resistance when melting without compromising the transparency of the obtained polarizer protective film, and preferably inorganic microparticles.
[0391] These particles can be used alone or in combination of two or more.
[0392] It can also achieve a high degree of transparency and lubricity by using particles with different sizes and shapes (such as needle-like and spherical).
[0393] Among the compounds constituting the above-mentioned particles, silica with excellent transparency (haze) is particularly preferred because its refractive index is close to that of the above-mentioned cycloolefin polymers, acrylic polymers or cellulose ester polymers.
[0394] As specific examples of silica, commercially available products with trade names such as AEROSIL (registered trademark) 200V, AEROSIL (registered trademark) R972V, AEROSIL (registered trademark) R972, R974, R812, 200, 300, R202, OX50, TT600, NAX50 (all of which are manufactured by AEROSIL Corporation of Japan), SEAHOSTAR (registered trademark) KEP-10, SEAHOSTAR (registered trademark) KEP-30, SEAHOSTAR (registered trademark) KEP-50 (all of which are manufactured by Nippon Catalyst Co., Ltd.), SYLOPHOBIC (registered trademark) 100 (manufactured by FUJI SILYSIA Co., Ltd.), Nipsil (registered trademark) E220A (manufactured by NihonSilica Industry Co., Ltd.), and ADMAFINE (registered trademark) SO (manufactured by ADMATECHS Co., Ltd.) are preferred.
[0395] As for the shape of the particles, there are no particular restrictions on using amorphous, needle-shaped, flat, spherical, etc. In particular, the polarizer protective film obtained by using spherical particles has good transparency and is therefore preferred.
[0396] If the size of the particles is close to the wavelength of visible light, light scattering will occur and transparency will decrease. Therefore, it is preferable to have a particle size smaller than the wavelength of visible light, and more preferably less than 1 / 2 of the wavelength of visible light.
[0397] If the particle size is too small, it may not be able to improve lubricity, so a size of 80 to 180 nm is particularly preferred.
[0398] It should be noted that when the particle size is an aggregate of primary particles, it refers to the size of the aggregate.
[0399] In addition, when the particle is not spherical, it refers to the diameter of the circle that is equivalent to its projected area.
[0400] The microparticles are preferably added in the range of 0.05 to 10% by mass, more preferably 0.1 to 5% by mass, relative to the base polymer (resin).
[0401] 6. Applications of polarizing protective film
[0402] The polarizer protective film manufactured by the method of the present invention can also be used as a phase difference film, and is suitable for use as a protective film for polarizers, etc. It can be used in various optical measuring devices and display devices such as liquid crystal display devices and organic electroluminescent display devices.
[0403] 7. Other
[0404] (7.1) Water contact angle (wettability)
[0405] In this invention, from the viewpoint of the adhesion between a polyvinyl alcohol-based film (polarizing film) and a polarizing protective film containing a cyclic olefin polymer, the water contact angle of the film is preferably in the range of 75 to 85° under the following measurement conditions.
[0406] (Determination of water contact angle)
[0407] In this invention, the water contact angle is measured by placing the sample in an atmosphere of 23°C and 55% relative humidity for 24 hours, and then using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., trade name DropMaster DM100) with 1 μL of pure water added for 1 minute in an atmosphere of 23°C and 55% relative humidity.
[0408] It should be noted that five measurements were performed, and the average value of the measurements was taken as the water contact angle.
[0409] (7.2) Surface layer density of the membrane
[0410] In this invention, from the viewpoint of membrane adhesion, a surface layer density of 1.9–2.0 g / cm³ is preferred. 3 .
[0411] Here, in this invention, "surface layer density" refers to the average density per unit volume of the region extending from the surface along the thickness direction to 100 nm (0.1 μm).
[0412] The average density can be calculated using the X-ray reflectance method (XRR) as described in paragraphs
[0011] to
[0018] of Japanese Patent No. 4921612.
[0413] When X-rays are incident on the membrane at a very shallow angle, they are totally reflected.
[0414] When the angle of incident X-rays is above the critical angle of total internal reflection, the X-rays penetrate into the membrane and are divided into transmitted waves and reflected waves at the membrane surface and interface, and the reflected waves interfere.
[0415] The density of the film can be determined analytically by analyzing the critical angle of total internal reflection, and the average density can be obtained by taking the average value of each angle.
[0416] (Method for determining average density based on X-ray reflectance (XRR))
[0417] The average density in the region from the surface along the thickness direction to 100 nm (0.1 μm) is determined by measuring the reflectivity of X-rays under the measurement conditions described below, and the critical angle of total internal reflection θc is obtained. The density ρ is calculated from this value. Then, for this density ρ, the distribution (density distribution) in the thickness direction in the region from the surface along the thickness direction to 100 nm (0.1 μm) is obtained, and the average value of this density distribution is calculated as the average density.
[0418] The measuring apparatus and measuring conditions are as follows.
[0419] Measurement Apparatus: Horizontal X-ray Diffraction Apparatus for Thin Film Evaluation, manufactured by Rigaku Co., Ltd.
[0420] Measurement conditions:
[0421] X-ray source; Cu-Kα1 (wavelength: )
[0422] Optical system: parallel beam optical system
[0423] Incident-side slit system: Ge(220)2 crystal, height-limiting slit 5mm, incident slit 0.05mm.
[0424] Light-receiving slit system: Light-receiving slit 0.10mm, Sola slit 5°
[0425] Detector: Blink Counter
[0426] Tube voltage and tube current: 45kV · 200mA
[0427] Scan axis: 2θ / θ
[0428] Scanning mode: Continuous scan
[0429] Scan range: 0.1-3.0 deg.
[0430] Scanning speed: 1 deg / min.
[0431] Sampling interval: 0.002° / step
[0432] (7.3) Stress at the fracture point
[0433] The fracture point stress is an indicator of the force that causes a membrane to break when it is continuously stretched in a certain direction. By increasing the fracture point stress in the long side direction, it is possible to suppress breakage and deformation in the membrane's transport and processing.
[0434] In this invention, the amount of residual solvent before the second stage of stretching needs to be in the range of 0.1 to 0.5% by mass. From the viewpoint of suppressing the formation of a high-density layer on the membrane surface, the more residual solvent, the better. However, if the membrane is stretched with more than 0.5% by mass of residual solvent, the amount of adhesive penetration will be excessive relative to the fabricated membrane, and the strength of the membrane will be weakened.
[0435] In the manufacturing method of the present invention, the stress at the breaking point can be increased by conveying the film at a conveying speed V2 satisfying the following formula (1) and keeping the amount of residual solvent in the range of 0.1 to 0.5% by mass before stretching in the second stage.
[0436] Equation (1): V1 < V2
[0437] In this invention, the fracture stress is preferably in the range of 2.1 to 2.7 GPa, and from the viewpoint of membrane strength, it is preferably 2.4 to 2.7 GPa.
[0438] (Method for determining the stress at the fracture point)
[0439] Specifically, for the determination of the fracture point stress of the polarizing protective film involved in this invention, a strip with a length of 70 mm (TD: width direction) × 10 mm (MD: long side direction) is cut from the polarizing protective film. A tensile test is performed using a Tensilon tensile testing machine (Orientec, RTC-1225A) at room temperature of 23°C and relative humidity of 55%, with an initial tensile chuck distance of 50 mm and a tensile speed of 50 mm / min. The stress is then determined based on the load-strain curve obtained.
[0440] It should be noted that the determination was performed 5 times for each sample, and the average value was used for evaluation.
[0441] At this point, by setting the stress at the fracture point in the long side direction of the polarizer protective film to 2.1 GPa or higher, it is possible to suppress fracture and deformation when force is applied to the long side direction of the film, and to easily suppress the reduction in yield and the reduction in optical properties or quality of the obtained film caused by the fracture and deformation of the film.
[0442] Example
[0443] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto. It should be noted that the use of "parts" or "%" in the examples, unless otherwise specified, means "parts by mass" or "% by mass".
[0444] <Fabrication of Polarizing Protective Film>
[0445] (Production of Polarizing Protective Film No. 1)
[0446] Solution casting is used to fabricate protective films for polarizing filters.
[0447] [Raw Material Membrane Manufacturing Process]
[0448] (Coating preparation process (S1))
[0449] <Synthesis of Cyclic Polyolefin Polymer P-1>
[0450] 100 parts by weight of purified toluene and 100 parts by weight of methyl norborneol carboxylate were added to a stirring device.
[0451] Next, 25 mmol% (relative to monomer mass) of ethyl hexanoate-Ni dissolved in toluene, 0.225 mol% (relative to monomer mass) of tri(pentafluorophenyl)boron, and 0.25 mol% (relative to monomer mass) of triethylaluminum dissolved in toluene were added to the stirring device.
[0452] React at room temperature with stirring for 18 hours.
[0453] After the reaction is complete, the reaction mixture is added to excess ethanol to form a polymer precipitate.
[0454] The polymer (P-1) obtained by precipitation purification was dried at 65°C for 24 hours under vacuum.
[0455] <Preparation of Coating D-1>
[0456] The following composition 1 is added to a mixing tank and stirred to dissolve the components. The coating is then prepared by filtering the mixture using filter paper with an average pore size of 34 μm and a sintered metal filter with an average pore size of 10 μm.
[0457] (Composition 1)
[0458] Cyclic polyolefin polymer (P-1) 150 parts by weight
[0459] 380 parts by weight of dichloromethane
[0460] 70 parts by weight of methanol
[0461] Next, the following composition 2, containing the cyclic polyolefin solution (coating) prepared by the above method, is fed into a disperser to prepare a particulate dispersion (M-1) as an additive.
[0462] (Composition 2)
[0463]
[0464] Mix 100 parts by weight of the above cyclic polyolefin solution and 0.75 parts by weight of the particulate dispersion to prepare a coating for film forming (polymer (resin) composition cyclic olefin polymer: COP).
[0465] (Cast casting process (S2))
[0466] The coating (polymer (resin) composition cyclic olefin polymer: COP) prepared in the coating preparation process (S1) is fed to the casting die head through a conduit by a pressurized quantitative gear pump. The coating is cast from the casting die head to the casting position on a support made of an infinitely conveying rotary-driven stainless steel annular belt with a width of 1800 mm using a film-forming production line. The coating is heated on the support until it becomes self-supporting, and the solvent evaporates until the wet film can be peeled off from the support by a peeling roller to dry it, thereby forming a wet film.
[0467] At this time, the coating conveying speed V1 is 40 m / min.
[0468] (Stripping process (S3))
[0469] After a wet film is formed in the casting process (S2), the wet film is peeled off from the support using a peeling roller while maintaining its self-supporting state.
[0470] (The process of stretching the wet film in the first stage relative to the width of the wet film immediately after casting (S4))
[0471] The density of the wet film is increased by subjecting it to high-temperature treatment without maintaining its width, causing the wet film to shrink in the width direction while undergoing the first stage of stretching.
[0472] At this point, the amount of residual solvent before the first stage of stretching was measured, and the result was 12% by mass.
[0473] In addition, it is implemented with a stretch ratio of 1.50.
[0474] (Drying process (S5))
[0475] Then, the wet film is heated on the support to evaporate the solvent.
[0476] (First cutting process (S6))
[0477] Cut off both ends of the stretched wet film in the width direction.
[0478] (First winding process (S7))
[0479] The membrane is conveyed at a speed of V1 (40 m / min) while being wound onto a core using a winding device.
[0480] Implement with an initial tension of 50N, a taper of 70%, and a corner of 25%.
[0481] [Processing steps]
[0482] (Stage 2 stretching process (S9))
[0483] Then, the wound film is pulled out of its roll (S8) and is conveyed in the stretching device at a conveying speed V2 (65 [m / min]) while undergoing the second stage stretching.
[0484] At this point, the amount of residual solvent before the second stage of stretching was measured, and the result was 0.30% by mass.
[0485] In addition, it is implemented with a stretch ratio of 1.50.
[0486] (Second cutting process (S10))
[0487] Similar to the first cutting process, both ends of the stretched film in the width direction are cut off.
[0488] (Second winding process (S11))
[0489] The above-mentioned film is wound up.
[0490] Implement with an initial tension of 50N, a taper of 70%, and a corner of 25%.
[0491] The above steps are used to manufacture the No.1 polarizing protective film.
[0492] It should be noted that the polarizing protective film produced by the above process has a thickness of 40 μm.
[0493] In addition, the water contact angle, surface layer density, and fracture stress of the polarizing protective film No.1 were measured, and each value was evaluated.
[0494] (Fabrication of polarizing protective films No. 2-15)
[0495] According to Table I, the conveying speed V1 of the coating as the stretching condition for the first stage, the amount of residual solvent and the stretching ratio before the first stage stretching, and the conveying speed V2 of the film as the stretching condition for the second stage, the amount of residual solvent and the stretching ratio before the second stage stretching are changed. Otherwise, the polarizing protective films No.2 to No.15 are manufactured in the same order as polarizing protective film No.1.
[0496] In addition, the water contact angle, surface layer density, and fracture stress of the polarizing protective films No.2 to No.15 were measured and evaluated.
[0497] [Water contact angle]
[0498] (Determination Method)
[0499] The water contact angle was measured by placing the sample in an atmosphere of 23°C and 55% relative humidity for 24 hours, and then using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., trade name DropMaster DM100) to add 1 μL of pure water for 1 minute in an atmosphere of 23°C and 55% relative humidity.
[0500] It should be noted that five measurements were performed, and the average value of the measurements was taken as the water contact angle.
[0501] The methods for determining the surface layer density and fracture point stress of the membrane are as described above and are therefore omitted.
[0502] The measured values and their evaluations are shown in Table I.
[0503] In addition, the evaluation criteria mentioned above are shown below.
[0504] (Evaluation Criteria)
[0505] 〇: The water contact angle is within the range of 75° to 85°.
[0506] △: Water contact angle greater than 85° and less than 88°
[0507] ×: Water contact angle greater than 88° and less than 90°
[0508] It should be noted that values outside the above range (values less than 75° or greater than 90°) were not calculated as measured values and are therefore excluded from the above evaluation range.
[0509] [Surface layer density of the membrane]
[0510] (Determination Method)
[0511] The method for determining the surface layer density of the membrane is as described above and is therefore omitted.
[0512] (Evaluation Criteria)
[0513] 〇: Surface layer density is 1.8–2.0 g / cm³ 3 Within the range
[0514] △: Surface layer density greater than 2.0 g / cm³ 3 And it is 2.1 g / cm³ 3 the following
[0515] ×: Surface layer density greater than 2.1 g / cm³ 3
[0516] It should be noted that values outside the above range (less than 1.8 g / cm³) 3 The value of was not calculated as a measured value, and therefore it was excluded from the scope of the above evaluation.
[0517] [Strress at the fracture point]
[0518] (Determination Method)
[0519] The method for determining the stress at the rupture point of the membrane is as described above and is therefore omitted.
[0520] (Evaluation Criteria)
[0521] 〇: The fracture point stress is in the range of 2.4 to 2.7 GPa.
[0522] △: The stress at the fracture point is above 2.1 GPa and less than 2.4 GPa.
[0523] ×: The stress at the fracture point is less than 2.1.
[0524] It should be noted that values outside the above range (values greater than 2.7 GPa) were not calculated as measured values and are therefore excluded from the above evaluation range.
[0525] Table I
[0526]
[0527] [Adhesion]
[0528] (Evaluation Method)
[0529] In addition, polarizers were fabricated using the obtained polarizer protective films No.1 to 15 according to the following method, and their adhesion to the polarizer layer was evaluated respectively.
[0530] (Adhesion between polarizer layer and polarizer protective film)
[0531] (1) Fabrication of the polarizer layer (polarizing film)
[0532] A 70 μm thick polyvinyl alcohol film was swollen in water at 35 °C.
[0533] The membrane was immersed in an aqueous solution consisting of 0.075 g of iodine, 5 g of potassium iodide and 100 g of water for 60 seconds, and then immersed in an aqueous solution at 45°C consisting of 3 g of potassium iodide, 7.5 g of boric acid and 100 g of water.
[0534] The above-mentioned film was subjected to uniaxial stretching at a stretching temperature of 55°C and a stretching ratio of 5 times.
[0535] After washing the uniaxial stretched film with water, it was dried to obtain a polarizer layer with a thickness of 20 μm (polarizing film: polyvinyl alcohol-iodine polarizer layer).
[0536] (2) Preparation of adhesive
[0537] (Preparation of water-based adhesives)
[0538] Dissolve 4 parts by weight of acetoacetyl-modified polyvinyl alcohol (Gohsefimer Z-200 manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) and 4 parts by weight of sodium glyoxylate (SPM-01 manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) in 100 parts by weight of water to prepare water-based adhesive A.
[0539] (Preparation of UV-curable adhesives)
[0540] After mixing the following components, degassing is performed to prepare a UV-curable adhesive.
[0541] It should be noted that triarylsulfonium hexafluorophosphate is formulated into a 50% propylene carbonate solution, and the solid content of triarylsulfonium hexafluorophosphate is described below.
[0542] (Element)
[0543]
[0544] (3) Fabrication of polarizing film
[0545] Prepare the optical films No.1 to No.12 produced above, and perform corona discharge treatment on their surfaces.
[0546] It should be noted that the conditions for corona discharge treatment are a corona output intensity of 2.0 kW and a linear velocity of 18 m / min.
[0547] Next, when using a water-based adhesive as an adhesive on the corona discharge treated surface of the membrane, the adhesive layer is formed by coating it with a rod coater with a film thickness of approximately 3 μm.
[0548] In addition, when using a UV-curable adhesive as the adhesive, the adhesive layer is formed by applying it with a bar coater in such a way that the cured film thickness based on UV irradiation is about 3 μm.
[0549] The polyvinyl alcohol-iodine polarizer layer is bonded to the adhesive layer obtained by the above operation.
[0550] Optical films No. 1 to 12 are also bonded to the other side of the polarizer layer to create a polarizer.
[0551] Next, when using a UV-curing adhesive, UV light is irradiated from both sides of the laminate using a UV irradiation device with a conveyor belt (using D-valve lamps manufactured by FUSION UV SYSTEMS) to achieve a cumulative light intensity of 750 mJ / cm². 2 This allows the UV-curable adhesive layer to cure.
[0552] The resulting laminates were dried in an oven at 90°C for 10 minutes to obtain a polarizer with a laminated structure containing a polarizer protective film.
[0553] (4) Evaluation of adhesiveness
[0554] Using the polarizer obtained by the above operation, the peel strength (adhesion) when peeling at the interface between the protective film of the polarizer and the polarizer layer is measured by a 90° peel test (according to JIS Z0237:2009) using a 90° peel test fixture (P90-200N) manufactured by Imada Co., Ltd. at an environment of 23°C and 55%RH.
[0555] In addition, the following evaluation criteria will be used for evaluation. If the score is △ or above, it will be judged as good.
[0556] The evaluation results are shown in Table I.
[0557] (Evaluation Criteria)
[0558] ○: Peel strength is 2.0 (N / 25mm) or higher.
[0559] △: Peel strength within the range of 1.0 to 2.0 (N / 25mm)
[0560] ×: Peel strength less than 1.0 (N / 25mm)
[0561] As shown in Table I, the embodiments are superior to the comparative examples in general.
[0562] Industrial availability
[0563] A method for manufacturing a polarizer protective film containing a cyclic olefin polymer that improves adhesion to polyvinyl alcohol-based films is provided.
[0564] Symbol Explanation
[0565] 1.1a Agitator (Agitator Tank)
[0566] 2 casting die head
[0567] 3. Support structure (ring belt, roller)
[0568] Rollers 3a and 3b
[0569] 4 peeling rollers
[0570] 5. Wet film
[0571] 6. Tensioning device
[0572] 7. Drying device
[0573] 8 Cutting section
[0574] 9 winding devices
[0575] 10 Tensioning devices
[0576] 11 Cutting section
[0577] 12 winding device
[0578] F membrane
Claims
1. A method for manufacturing a polarizing protective film, characterized in that, The polarizer protective film contains a cyclic olefin polymer. The manufacturing method includes a raw material membrane manufacturing process and a processing process. The raw material film manufacturing process comprises at least the following steps: a step of casting the coating material onto a support at a conveying speed V1 to form a wet film; a step of stretching the wet film relative to the width of the freshly cast wet film in a first stage; and a step of winding the film formed by drying the wet film. The residual solvent content before the first stage of stretching is in the range of 1% to 15% by mass. The processing step includes conveying the wound film at a conveying speed V2 to meet the following formula (1) and performing a second-stage stretching. Equation (1): V1 < V2 Furthermore, in the process of stretching the wound film in the second stage, the winding width is stretched within the range of 0.1 to 0.5% by mass of residual solvent before the second stage stretching is to be performed.
2. The method for manufacturing the polarizing protective film according to claim 1, characterized in that, The stretching ratio in the first stage stretching process is in the range of 1.1 to 2.0 times.
3. The method for manufacturing the polarizing protective film according to claim 1 or 2, characterized in that, The stretching ratio in the second stage stretching process is in the range of 1.1 to 2.0 times.
Citation Information
Patent Citations
JP1974021612A
Sticking of printing spacer
JP1988250028A
Ferroelectric memory device
JP2000004000A
Retardation film, method for manufacturing the same and elliptical polarization plate
JP2002311240A
Polyvinyl alcohol film and polarizing film
JP2003248123A
